L-band multi-wavelength brillouin-raman fiber laser with 20-GHz channel spacing - Abass A.K.; Al-Mansoori M.H.; Jamaludin M.Z.; Abdullah F.; Al-Mashhadani T.F.; Ali M.H. (Taylor and Francis Inc., 2023)
A tunable multi-wavelength L-band Brillouin-Raman fiber laser with a 20-GHz channel spacing utilizing bidirectional ring cavity is proposed and experimentally investigated. The laser employs a co-pumped dispersion compensating fiber as a gain medium for both Brillouin and Raman gains. With a Raman pump of 425 mW, the laser system can generate up to 12 double-spaced Brillouin Stokes signals. This simple laser configuration provides stable Brillouin Stokes signals in the absence of self-lasing cavity modes with a tuning range exceeding 35 nm without using any filtering mechanism. The Stokes signals have more than 20 dB of optical signal-to-noise ratio. Copyright © Taylor & Francis Group, LLC.